POST-MARKETING DRUG SAFETY RESEARCH: ANALYSIS OF RECOMMENDATIONS OF FOREIGN REGULATORS - E. V. Shubnikova; T. M. Bukatina; D. A. Kaperko; N. Yu. Velts; M. A. Darmostukova; A. S. Kazakov; I. I. Snegireva; E. O. Zhuravleva; G. V. Kutekhova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
The monitoring of information on the safety of various drugs is becoming more relevant day by day, as the number of drugs on the  pharmaceutical market increases, generic drugs, bio-analogous drugs appear. Long-term post-marketing use of a  medicinal product allows to accumulate a sufficient evidence base  and experience of application in various population groups, to study  the features of the use of this drug. Information on the safe use of  new drugs can be obtained in selected scientific publications. In  addition to publications in the specialized scientific literature,  regulators of different countries on the basis of new information give opinions on the need to make changes in instructions for medical  use. When analyzing the recommendations of Russian and foreign  regulatory authorities on restricting the circulation of medicines and  / or the need to amend the instructions for their medical use in  connection with the change in the assessment of the safety profile,  we identified 16 administrative decisions of foreign regulatory bodies containing information about the following drugs registered in  Russia. We consider all recommendations to be important  information on the safety of medicines, which is addressed to  specialists in the field of medicine, in particular to persons  authorized by pharmacovigilance in pharmaceutical companies. In  addition, this information may be of interest to physicians of various  specialties who in their practice use buprenorphine, venlafaxine,  gadolinium contrast drugs hydroxyethyl starch, daclizumab,  duloxetine, denosumab, cladribine, clomifene citrate, milnacipran, methotrexate, pemetrexet, radium dichloride, rifampicin,  phoebusostat, flupirtine.